(untitled) (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2025)
Interfaith harmony is a fundamental aspect in creating social stability in a pluralistic society. In this context, the concept of Ashabiyyah introduced by Ibn Khaldun has significant relevance in understanding the dynamics of group solidarity and how it can contribute to social harmony. Ashabiyyah is basically a bond of solidarity and unity in a group that can function as a strengthening factor in building social and political stability. However, if Ashabiyyah develops in an exclusive and fanatical form, the potential for conflict between groups will increase. This study aims to examine the relevance of the concept of Ashabiyyah in building harmony between religious communities by examining the thoughts of Ibn Khaldun. This study uses a qualitative research method with a descriptive-analytical approach. The main data sources in this study are the works of Ibn Khaldun, especially the Muqaddimah, as well as secondary literature that discusses the relationship between Ashabiyyah and social harmony in a multicultural society. The results of the study show that Ashabiyyah can be a unifying force if it is developed in an inclusive form, where solidarity is not only limited certain primordial groups but also encompasses the wider community, including in relations between religious communities. Ibn Khaldun emphasized that a civilization will last long if it has a strong Ashabiyyah that is able to embrace various elements of society. Conversely, if Ashabiyyah only focuses on the interests of certain groups without paying attention to social harmony, then conflict and division will occur more easily. This study also highlights the importance of wise leadership in managing Ashabiyyah so that it does not turn into a tool of domination by one group over another. The government and religious leaders have an important role in building an inclusive collective consciousness by instilling the values ​​of unity, tolerance, and social justice. Thus, Ashabiyyah can be optimized as an instrument to strengthen brotherhood between religious communities and create stability in a plural society. This study contributes to understanding how Ibn Khaldun’s thoughts on Ashabiyyah can be applied in a modern context to manage religious and cultural diversity. The implication of this study is the need for social policies that encourage integration and togetherness between groups without eliminating their respective identities, so that a harmonious and just life is created.